K. Hovnanian's approach to preserving intangible assets after acquisitions - Caligiuri, Paula (SAGE knowledge. Cases., 2016)
This case study examines homebuilder K. Hovnanian's approach to acquisitions, with a focus on how the organization retains key intangible assets - such as leaders' knowledge and social capital - of their acquired companies. It introduces learners to the HR and business strategy issues associated with acquisitions. By the end of the case study, students will be able to identify HR's role in retaining intangible assets during a strategic acquisition; understand the challenges to managing acquisitions when retaining key intangible assets is a strategic goal; develop HR strategies and implementation plans to integrate the intangible assets of both organizations; and address key HR challenges during the post-acquisition phase.